2009
DOI: 10.1016/j.molcel.2009.02.022
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Receptor with Two Associating Transmembrane Domains on the Cell Surface: Integrin αIIbβ3

Abstract: Structures of intact receptors with single-pass transmembrane (TM) domains are essential to understand how extracellular and cytoplasmic domains regulate association and signaling through TM domains. A chemical and computational method to determine structures of the membrane regions of such receptors on the cell surface is developed here and validated with glycophorin. An integrin heterodimer structure reveals association over most of the lengths of the α and β TM domains, and that the principles governing ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
228
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(253 citation statements)
references
References 40 publications
22
228
2
1
Order By: Relevance
“…S5), indicating that both CD 3 CN/H 2 O mixture and bicelles provide environments compatible for TM complex assembly. Many different computational models of integrin TM complexes have been proposed (3-5, 11, 13, 15-18), but the 2 most recent ones (17,18) were found to be similar to the structure of Lau agreement for integrin TM assembly from the latest independent studies (including ours) using different methods.…”
Section: Correlation Of the Tmcd Interface With Integrin Mutation Datmentioning
confidence: 63%
See 1 more Smart Citation
“…S5), indicating that both CD 3 CN/H 2 O mixture and bicelles provide environments compatible for TM complex assembly. Many different computational models of integrin TM complexes have been proposed (3-5, 11, 13, 15-18), but the 2 most recent ones (17,18) were found to be similar to the structure of Lau agreement for integrin TM assembly from the latest independent studies (including ours) using different methods.…”
Section: Correlation Of the Tmcd Interface With Integrin Mutation Datmentioning
confidence: 63%
“…S5), the different CT clasps (Fig. S5) involving either the ␣IIb KVGFF reverse turn or helix cannot be due to the lack of TM as stated by Zhu et al (17). Rather, different solvent systems (CD 3 CN/H 2 O vs. bicelles) in the 2 studies may have captured 2 different conformational states of an intrinsically flexible region.…”
Section: Correlation Of the Tmcd Interface With Integrin Mutation Datmentioning
confidence: 69%
“…1B) (19). Mutations most disruptive of the DN effect of the β 3 helix occurred at residues L697, V700, I704, and G708, each of which has been identified as important for stabilizing the resting conformation of full-length α IIb β 3 (2-4, 6, 7), and in addition, are in proximity to α IIb based on disulfide-cross-linking and NMR measurements (11,12). The DN-ToxRed assay was then used to probe the association of the β 3 subunit with its other partner, α v , as well as the association of the β 1 TM domain with its partners α 2 and α 5 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…If this is the case, one might expect that the TM helices would form an autonomous interaction unit, engaging in a stable interaction even in the absence of extracellular and cytoplasmic domains. Indeed, early modeling studies suggested a specific geometric interaction (4, 9, 10), which has recently been supported by NMR and Cys cross-linking studies of the α IIb and β 3 TM helices (11,12).…”
mentioning
confidence: 87%
“…inside-out signaling (Dai et al, 2015;Ginsberg et al, 2005). The activation states of integrins are tightly controlled by interactions between α-and β-subunits at both the membrane-proximal cytoplasmic tails (CTs) and the transmembrane domains (Vinogradova et al, 2002;Yang et al, 2009;Zhu et al, 2009). Integrin conformational changes toward active states can be triggered by the binding of cytoplasmic integrin activators to the integrin β CTs (Liu et al, 2000;Ma et al, 2007;Moser et al, 2009b;Qin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%